Efektivitas Media Mathematical Intelligence Stick untuk Meningkatkan Operasi Hitung Penjumlahan pada Peserta Didik Diskalkulia - Syafrianis; Arisul Mahdi; Mega Iswari; Syari Yuliana (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This article aims to examine the effectiveness of the Mathematical Intelligence Stick media in improving the ability of addition operations with the storage technique in dyscalculic students. This study uses a quantitative approach with the Single Subject Research (SSR) method through an A–B–A design. Data collection was carried out using a performance test given at each research session, in the form of ten addition problems with the storage technique adjusted to the students' abilities. The data obtained were analyzed using visual graphic analysis by paying attention to changes in ability levels, directional trends, and data stability in each condition. The results showed that in the baseline condition (A1) the students' abilities were at 0%. After being given an intervention using the Mathematical Intelligence Stick media in the intervention condition (B), the students' abilities increased significantly from 70% to 100%. In the baseline condition (A2), the students' abilities remained in the range of 90%–100%. These findings indicate that the Mathematical Intelligence Stick media is effective in improving the ability of addition operations with the storage technique in dyscalculic students.